Influence of Humidity on Fiber Bragg Grating Sensors - Ander Montero; Gotzon Aldabaldetreku; Gaizka Durana; Iagoba Jorge; Idurre Sáez de Ocáriz; Joseba Zubia (Advances in Materials Science and Engineering)
We demonstrate the influence of the relative humidity (RH) on the wavelength of fiber Bragg grating sensors (FBGS), performing tests with five FBGS at different humidity and temperature conditions. These tests were performed in a climate chamber whose RH changes according to a scheduled profile from 30% to 90%, in steps of 10%. These profiles were repeated for a wide range of temperatures from 10∘C to 70∘C, in steps of 10∘C. Two different types of instrumentation methods have been tested, spot welding and epoxy bonding, in two different materials, steel and carbon fiber reinforced polymer (CFRP). We discuss the results for each type of sensor and instrumentation method by analyzing the linearity of the Bragg wavelength with RH and temperature.